Proceedings of the Thirteenth Conference on Applied Linguistics (CONAPLIN 2020) 2021
DOI: 10.2991/assehr.k.210427.022
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Students’ Learning Engagement in EFL Online Classroom

Abstract: Due to the pandemic era, the Indonesian government proposes all schooling through online learning, including learning English. The study of students' engagement in EFL online learning is scarce in Indonesia. The aim of this study investigates students' engagement in EFL online classrooms in a vocational school, Indonesia through a descriptive survey. The obtained data were analysed, drawing upon the Online Student Engagement Scale (OSE) proposed by Dixson (2015). The scale includes four categories: behaviour, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…Research on student engagement has received attention not only in the physical classroom, but also in the online learning environment. Student engagement refers to students’ cognitive investment, active participation in their learning and emotional commitment to it (Suharti et al, 2021 ; Zepke et al, 2009 ). Student engagement is dependent on the learning activities designed by the teachers in the online environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on student engagement has received attention not only in the physical classroom, but also in the online learning environment. Student engagement refers to students’ cognitive investment, active participation in their learning and emotional commitment to it (Suharti et al, 2021 ; Zepke et al, 2009 ). Student engagement is dependent on the learning activities designed by the teachers in the online environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research evidence has proven that student engagement might have a significant impact on students' learning and performance in an online environment. Suharti et al, (2021), for instance, reported that students' active engagement improved their interest, motivation, and satisfaction with their learning outcomes, assisting them in studying more effectively and achieving higher academic results. Meyer (2014) and Britt et al (2015) also viewed student engagement as evidence of their considerable effort for cognitive development and ability to construct knowledge, contributing to high achievement.…”
Section: Importance Of Learners' Engagement In Online Classesmentioning
confidence: 99%
“…Student engagement, also known as student involvement or participation, has been getting more concern thanks to Astin's publication in 1984. Previously conducted studies with a focus on student engagement have established conceptual frameworks, particularly in relation to student involvement (Astin, 1984), and student engagement (Kuh, 2003). Learners' engagement in online learning has received increasing interest from researchers with more studies investigating learners' engagement and learners' and/or teachers' perceptions of student engagement in online learning (e.g., Sari, 2020;Oraif & Elyas, 2021;Suharti et al, 2021). Findings from this research body have identified learner engagement as a key factor contributing to their active involvement in learning and academic achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some schools and students are unfamiliar with online learning, it does not automatically translate into low participation. Some studies revealed a high level of engagement in online learning during the pandemic situation (Oraif & Elyas, 2021;Rojabi, 2020;Suharti et al, 2021). Some also suggested an evaluation of online learning since it did not promote student engagement (Dumford & Miller, 2018;Mukhtar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most recent studies on engagement in online learning only explored students' perspectives (Oraif & Elyas, 2021;Rojabi, 2020;Suharti et al, 2021) and some faculty members (Bolliger & Martin, 2018;Mukhtar et al, 2020;Wang & BrckaLorenz, 2018), with only a few studies explored from both teachers' and student's perspective. As teachers also carry a substantial role in Since the worldwide pandemic, there has been more focus on the trend of online learning replacing face-to-face instruction.…”
Section: Introductionmentioning
confidence: 99%